Influencia de las motivaciones en la desisión de compra y en la lealtad hacia Internet - Carla Ruiz Mafé; Silvia Sanz Blas (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2006)
The growing importance of Internet as a complementary alternative to traditional retail outlets make it necessary to find out what motivates consumers to accept and use it as a purchase channel. This work therefore aims to analyse the main motivations for e-shopping and their influence on the purchase decision and future behaviour intentions. The results obtained suggest that convenience is the main reason for using Internet as a shopping channel and that the different utilitarian motivations analysed influence the volume of on-line expenditure, e-loyalty and willingness to pay a higher price than in traditional channels in exchange for the benefits of Internet shopping.
Keywords: 330; Internet; utilitarian motivations; hedonic motivations; E-loyalty; consumer behaviour